2001
DOI: 10.1002/j.2334-5837.2001.tb02417.x
|View full text |Cite
|
Sign up to set email alerts
|

5.7.2 The Data Standard AP‐233: An Invigorator for Global Systems Engineering

Abstract: Abstract. Contemporary systems engineering developments are frequently global in scope, and 'distributed' in both graphical and temporal senses, involving many different design and analysis tools, across systems engineering and various specialist engineering disciplines. Currently there is little interoperability between these suites of tools. This situation can have real stagnating effects on systems engineering activities, and considerable detrimental economic, productivity and quality consequences. Neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…• The scope of PDM systems are being extended into the system and software engineering domain as illustrated by the work of the SEDRES project (Johnson & Herzog, 2001) and most notably the PLCS standard, which includes basic support for representing requirements and system functionality. • The scope of UML is extended to provide more detailed support for non-software artifacts.…”
Section: Product Data In the Enterprisementioning
confidence: 99%
“…• The scope of PDM systems are being extended into the system and software engineering domain as illustrated by the work of the SEDRES project (Johnson & Herzog, 2001) and most notably the PLCS standard, which includes basic support for representing requirements and system functionality. • The scope of UML is extended to provide more detailed support for non-software artifacts.…”
Section: Product Data In the Enterprisementioning
confidence: 99%
“…More detail to the model, philosophy and evolution of the AP-233 design can be found in (Johnson, 1999;Johnson et al, 1999;Johnson et al, 2000;Pandikow et al, 2000;Johnson & Herzog, 2001;Herzog & Torne 2001). Scott et al (2002) have shown that AP-233 is well suited as a generic format for holding systems and software requirements and transferring them between dissimilar tools.…”
Section: Ap 233mentioning
confidence: 99%
“…In the authors view the projects were successful in components 1-3 in the sense that it was demonstrated that the information model along with supporting STEP parts could be used to exchange information between a number of commercial and proprietary tools (Johnson, 2001). The validation scenarios executed included data exchange between tools used in the same phase in the engineering process (Statemate ↔ Teamwork), and tools used throughout the engineering process (Labsys, StP, Demanda, with Doors used as a PDM system).…”
Section: Introductionmentioning
confidence: 99%